Problematika Pindah Agama Terhadap Keluarga Muallaf di Kecamatan Makale Tana Toraja - Yulianti (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
This study aims to determine the factors that cause a person to change religions in the Makale tana Toraja sub-district, to find out the problems of the converts' family in the Makale tana Toraja sub-district, and to find out the efforts made in overcoming the problems of the converts' families in the Makale Tana Toraja sub-district. The type of research used is descriptive qualitative research with linguistic, pedagogical, and sociological approaches. Researchers used two sources of data, namely primary data and secondary data. In the data collection method the researcher conducted observations, interviews and documentation. The procedures for carrying out the research are the preparation stage, the operational stage, and the completion stage. Data analysis with data reduction, data presentation, and data verification steps. The results of this study indicate that: First, the factors that cause a person to convert to religion in Makale Tana Toraja sub-district are caused by two elements, namely: himself, the innate factor, love is a feeling that is very valuable, the desire to love and be loved is a human nature and the best thing is that love is united in marriage, religious differences are often a problem in the sustainability of the household. External elements include; family factors, parental divorce, will have a negative impact on children, environmental factors can affect a person's conversion to religion, change in status and poverty factor. Second, the problem of the converts' family in the Makale tana Toraja sub-district. Among the several problems faced by converts, one of which is a problem in the harmony of a household. Of course, with his new identity as a Muslim, he will start new adaptations that will receive good and bad responses. Third, the efforts made to overcome the problems of converts' families in Makale Tana Toraja District.